Why Rural Matters: The Need for Every State to Take Action on Rural Education - Elizabeth Beeson (Journal of Research in Rural Education, 2000)
Fully one quarter ofAmerica's school-age children attend public schools in rural areas or small towns. But if you listen to the education policy debate, chances are you will not hear much about them. In most ofthe 50 states, it is the education ofurban children that gets nearly all ofthe attention. This report aims to adjust that picture by bringing rural schools and communities into focus. Rural kids, their schools, and their communities do matter. And in many states, action on behalfofrural schools needs to be an urgent priority.